Pola Perilaku Konsumen terhadap Keputusan Mengikuti Event K-Pop - Ramadhania, Almira Fidia; Setyaningrum, Idfi; Kartikasari, Cynthia Yohanna (Syntax Corporation, 2023)
The present Korean wave has become a worldwide phenomenon, even in Indonesia. Consumer behaviour changes toward numerous activities, including K-Pop events, have been noticed. Participation of fans in various K-Pop events and the purchase of things as a form of social identity associated with K-Pop provide not only economic value but also satisfaction and greater self-confidence for K-Pop lovers. As a result, the purpose of this research is to better understand the consumer behaviour patterns around the decision to attend BTS K-Pop events in Surabaya. Through interviews and observations, the research uses a qualitative descriptive method. According to the survey, K-Pop events are more than just a form of entertainment; they also represent huge commercial potential. The passion of K-Pop fanbases is critical not only in changing behavioural patterns in attending various K-Pop events but also in driving social changes and fostering enhanced self-confidence in network development.